SiC Conversion Coating Prepared from Silica-Graphite Reaction - Back-Sub Sung; Young-Hoon Yun (Advances in Materials Science and Engineering)
The β-SiC conversion coatings were successfully synthesized by the SiO(v)-graphite(s) reaction between silica powder and graphite specimen. This paper is to describe the effects on the characteristics of the SiC conversion coatings, fabricated according to two different reaction conditions. FE-SEM, FE-TEM microstructural morphologies, XRD patterns, pore size distribution, and oxidation behavior of the SiC-coated graphite were investigated. In the XRD pattern and SAD pattern, the coating layers showed cubic SiC peak as well as hexagonal SiC peak. The SiC coatings showed somewhat different characteristics with the reaction conditions according to the position arrangement of the graphite samples. The SiC coating on graphite, prepared in reaction zone (2), shows higher intensity of beta-SiC main peak (111) in XRD pattern as well as rather lower porosity and smaller main pore size peak under 1 μm.